The English East India Company : the study of an early joint-stock company, 1600-1640 - Chaudhuri, K. N. (Routledge/Thoemmes Press, 1999)
Introductory. The organization of the company and business decisions up to 1620. The years of crisis: organization and trade. The factors of the East India company...